Arterial vascular complications in peripheral extracorporeal membrane oxygenation support: a review of techniques and outcomes. (July 2013) - Roussel, Arnaud; Al-Attar, Nawwar; Khaliel, Feras; Alkhoder, Soleiman; Raffoul, Richard; Alfayyadh, Faisal; Rigolet, Marina; Nataf, Patrick
Peripheral venoarterial extracorporeal membrane oxygenation support provides prolonged support in the event of acute or acute-on-chronic cardiac and/or respiratory failure. This support serves as a bridge to recovery, decision-making, heart transplantation or ventricular-assist device implantation. It can be implanted either through a percutaneous approach using Seldinger's technique or via an open approach via the common femoral artery or the axillary artery. Early and late arterial vascular complications remain an important issue, with rates of up to 28% with femoral and axillary cannulation sites. Among them, limb ischemia requires prompt diagnosis and management to avoid limb amputation. In the case of peripheral artery cannulation, ipsilateral distal limb perfusion to prevent acute limb ischemia can be performed via a single lumen catheter through the artery or via the 'chimney graft' technique during extracorporeal membrane oxygenation implantation.